2015
DOI: 10.5812/ijhrba.22576
|View full text |Cite
|
Sign up to set email alerts
|

The Mortality Rate of Myocardial Infraction Patients With and Without Opium Dependen

Abstract: Background:Myocardial infarction (MI) is a heart condition caused by the suspension of blood circulation in a part of the myocardium. There are different risk factors contributing to a heart attack. Some believe that endorphins and endogenous opioids play an important role in causing MIs.Objectives:This study intended to determine the relationship between opium dependency and mortality rate among patients with MI.Patients and Methods:This retrospective study investigated patients who had MI for the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Research has demonstrated that opium use is not correlated with increased rates of post–MI mortality, morbidity, and readmission. 6 , 31 , 33 , 34 , 35 Nevertheless, a few investigators have reported remarkably longer hospital lengths of stay, 35 higher readmission rates, 36 and borderline significantly higher in-hospital mortality rates (11.5% vs. 5.9%; p = 0.072) 36 in opium-dependent patients with acute MI rather than non-opium users ( Table 2 ).…”
Section: Acute Coronary Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that opium use is not correlated with increased rates of post–MI mortality, morbidity, and readmission. 6 , 31 , 33 , 34 , 35 Nevertheless, a few investigators have reported remarkably longer hospital lengths of stay, 35 higher readmission rates, 36 and borderline significantly higher in-hospital mortality rates (11.5% vs. 5.9%; p = 0.072) 36 in opium-dependent patients with acute MI rather than non-opium users ( Table 2 ).…”
Section: Acute Coronary Syndromesmentioning
confidence: 99%
“…It has been shown in all previous studies that opium abusers smoke cigarettes more frequently. 10 , 36 , 48 Thus, it is not clear whether the association between opium consumption and CVDs is a dependent association confounded by smoking or opium consumption is an independent risk factor for CVDs. Numerous studies have tried to answer this question.…”
Section: Association Between Opium Consumption and Cardiovascular Dismentioning
confidence: 99%
“…Harati et al evaluated the relationship between opium use, mortality rate and cardiac arrest in 400 MI patients. They concluded there was no significant difference between addicted and non-addicted groups regarding the study outcomes, although opium users were more commonly hospitalized due to cardiac problems [56].…”
Section: Opium As An Impartial Factormentioning
confidence: 99%
“…Opium dependency decreased age by 3.6 years (95% CI = 1.2 to 6.0; P = 0.003) for the occurrence of post-MI mortality and morbidity independent of cigarette smoking. 33 Harati et al 34 observed that those with opium dependency had almost significantly higher in-hospital mortality (11.5% vs 5.9%; P = 0.072) and significantly higher rehospitalization rates than nonusers (38.5% vs 13.7%; P < 0.001). Currently, many physicians do not advise their patients to quit opium consumption because of the fear of inducing a heart attack.…”
Section: Acute Coronary Syndromesmentioning
confidence: 97%